(untitled) (Research, Society and Development, 2021)
The work presents an identification key for the species of the genus Aristolochia L. (Aristolochiaceae) of the state of Mato Grosso, Brazil, as well as morphological descriptions, taxonomic and phytogeographic comments, and detailed photographs of Aristolochia chiquitensis Duch., A. goudotii Duch. and A. hoehneana O.C.Schmidt. These three species are new records for the state and A. goudotii is a new record for Brazil. The study was conducted between February and May 2021. Material was collected in the municipalities of Alta Floresta and Nova Bandeirantes and specimens in the Herbário da Amazônia Meridional (HERBAM) were analyzed, collected in the municipalities of Colíder, Itaúba and Nova Canaã do Norte, in northern Mato Grosso. The morphological study was conducted in the Plant Morphology Laboratory in HERBAM at the State University of Mato Grosso, Alta Floresta University Campus, using a stereomicroscope and the usual utensils. The identification of the taxa, as well the elaboration of the dichotomous key, were conducted by taxonomists. The present work increases the number of Aristolochia species from 22 to 25 in Mato Grosso and 83 to 84 in Brazil, demonstrating the importance of field expeditions, botanical collections, and taxonomic studies to our knowledge of biodiversity.